2022
DOI: 10.1177/09564624221123869
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral and anal human papillomavirus infection in Czech predominantly HIV-positive men having sex with men - data from a previously unreported population

Abstract: Background: HIV-positive men who have sex with men (MSM) are more likely to experience human papillomavirus (HPV) infection. The persistent HPV infection is the major factor in the development of anal and oropharyngeal neoplasms. Data on the prevalence of anal and oral HPV in MSM are almost absent from the countries of Central and Eastern Europe. We conducted a cross-sectional study focused on the prevalence of oral and anal HPV infections and the relationship between current anal and oral HPV intrapersonal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
2
5
2
Order By: Relevance
“…Between 1995 and 2009, the five most prevalent types worldwide were HPV16, HPV18, HPV52, HPV31, and HPV58 46 . Similar to our result, HPV16 was the most prevalent HR‐HPV type in the Czech, 30 Vietnam 42 , and Japan 41 . In Shanghai, China, HPV16, HPV59, and HPV52 were the most popular HR‐HPVs, whereas the three most frequent LR‐HPVs were HPV6, HPV11, and HPV43 39 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Between 1995 and 2009, the five most prevalent types worldwide were HPV16, HPV18, HPV52, HPV31, and HPV58 46 . Similar to our result, HPV16 was the most prevalent HR‐HPV type in the Czech, 30 Vietnam 42 , and Japan 41 . In Shanghai, China, HPV16, HPV59, and HPV52 were the most popular HR‐HPVs, whereas the three most frequent LR‐HPVs were HPV6, HPV11, and HPV43 39 .…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of HPV among men varied between countries and crowds. The male HPV infection rates in Czech, Brazil, and Hong Kong were 96.8%, 80%, and 90%, respectively, [30][31][32] which were higher than that mentioned in our study. Furthermore, the infection rates of any genital HPV type in men were in Brazil (60.2%), Mexico (49.2%), and the United States (46.9%).…”
Section: Age Distribution In Hpv-positive Patientscontrasting
confidence: 80%
“…The most prevalent oral HPV types in these groups of MSM varied and included 33 19 /56/66/70 17 . In one study, HPV16 14 was the most common oral HPV type, while in another no men had HPV16 16 in the oral cavity. It is important to acknowledge the high prevalence of varied hrHPV types in this specific population to better understand HPV‐related head and neck cancer natural history.…”
Section: Discussionmentioning
confidence: 97%
“…While in our study, oral HPV prevalence was 11.1%, other studies carried out with MSM have found an oral HPV prevalence ranging from 6% to 33.9% (average 18.5%). [14][15][16][17][18][19] Two of these studies found an oral hrHPV prevalence of 2.4% 16 and 19.6%. 18 The most prevalent oral HPV types in these groups of MSM varied and included 33 19 /56/66/70.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 85–96% are caused by HPV-16 infections [ 1 ]. A recent study of 205 HIV-positive men who have sex with men (MSM) in the Czech Republic reported HPV in 96% of anal and 23% of oral samples, with HPV-16 being the most common genotype in both [ 2 ].…”
Section: Introductionmentioning
confidence: 99%